Accuracy of Ultrasound based BI-RADS Scoring System to Predict Malignancy in Patients with Breast Lump - Usman Rasheed, Saima Ameer, Rimsha Sadia Bukhari, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the diagnostic accuracy of BIRADS in diagnosing malignant breast lesions in patients with palpable breast lump. Patients and Methods: A total number of 100 patients presenting with Palpable breast lump were included in this study. The study was conducted in radiology unit of Lahore General Hospital Lahore from August-2021 to April-2022. Data regarding baseline study variables such as age, living area and socioeconomic status was collected for each patient. Ultrasound examination of the breast masses was done by an expert radiologist for calculation of BI-RADS score. Diagnosis of malignancy on histopathological findings was also made. Results: Mean age of patients was 41.04±11.00 years. There were 43 (43.0%) from rural areas and 57 (57%) from urban areas. Malignancy on BI-RADS was found in 42 (42%) patients. On evaluation of diagnostic accuracy of BI-RADS, BI-RADS was 92.5.0% sensitive, 88.3% specific having 84.1% PPV and 94.6% NPV (Table 1). Conclusion: When compared to histopathologic diagnosis, the findings of our study demonstrated that BIRADS is an accurate and trustworthy method for diagnosing breast lumps.